1994
DOI: 10.4319/lo.1994.39.5.1130
|View full text |Cite
|
Sign up to set email alerts
|

Chemical weathering of phosphate and germanium in glacial meltwater streams: Effects of subglacial pyrite oxidation

Abstract: Data from three glacial meltwater streams draining Mt. Tronador in the southern Argentine Andes (72"W, 4 1"s) show that subglacial pyrite oxidation and the subsequent precipitation of iron oxides strongly influence dissolved phosphate concentrations but do not appear to affect dissolved germanium concentrations. Total-Fe (TFe) and total-P (TP) concentrations are high in all three glacial streams, but the ratios of soluble reactive phosphate (SRP) to TP are very different, The Upper Manso Stream that drains the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 36 publications
3
43
1
Order By: Relevance
“…The potential for chemical weathering of glaciogenic sediment in proglacial environments also suggests that our estimate of the glacial Si flux is also conservative. Chillrud et al (1994) derived the Ge/Si ratio of a glacial meltwater stream of the Argentine Andes mountains, and found that these data agree well with those of global river data (Mortlock and Froelich, 1987). The highest Ge/Si ratio (1.35 pmol/Amol) measured by Chillrud et al (1994) derives from a water sample which had a Si concentration of f 36 Amol/l (see also Froelich et al, 1992).…”
Section: Reconstructing Hcosupporting
confidence: 67%
See 4 more Smart Citations
“…The potential for chemical weathering of glaciogenic sediment in proglacial environments also suggests that our estimate of the glacial Si flux is also conservative. Chillrud et al (1994) derived the Ge/Si ratio of a glacial meltwater stream of the Argentine Andes mountains, and found that these data agree well with those of global river data (Mortlock and Froelich, 1987). The highest Ge/Si ratio (1.35 pmol/Amol) measured by Chillrud et al (1994) derives from a water sample which had a Si concentration of f 36 Amol/l (see also Froelich et al, 1992).…”
Section: Reconstructing Hcosupporting
confidence: 67%
“…The Ge flux is calculated directly from the Si flux and hence the variation of the Ge flux is similar to that of the Si flux over the last deglaciation. Since glacial systems have higher Ge/Si ratios than those of non-glacial systems (Chillrud et al, 1994), the incorporation of the former increases the Ge flux by a maximum of f 10% (at 10 ka BP). No significant change in Si flux between the present day and the LGM is contrary to previous suggestions that Si fluxes were double at the LGM (Froelich et al, 1992).…”
Section: Si and Ge Fluxes: Effect On Global Average Riverine Ge/simentioning
confidence: 99%
See 3 more Smart Citations